Bound by steel and stone : the Colorado-Kansas Railway and the frontier of enterprise in Colorado, 1890--1960 - Bowers, J. Bradford, 1966- (Timberline books., 2021)
"Recounts the stories of those who attempted ventures on the Colorado-Kansas Railway, which survived in one form or another for nearly fifty years, overcoming competition from other railroads, a limited revenue base, and even more limited capital financing. Consisting of steam-powered locomotives traveling along a mere twenty-five miles of track" --